Effect Of Halal Tourism On Interest For Visit Of Tourists In Medan City - Dewi Andriany; Mutia Arda (Proceeding International Seminar of Islamic Studies, 2019)
Halal tourism is a kind of alternative for Islamic tourists who want to get not only tourism needs, but also spiritual needs. Halal tourism, not only for Muslim tourists, non-Muslim tourists are also allowed to enjoy halal tourism. This is the background of the need to develop tourism potential in the city of Medan, especially halal tourism, given the strategic location of Medan as one of the entrances to the trade area. The purpose of this study was to analyze the effect of halal tourism on the intention of visiting tourists in Medan. The population in this study are people who have stayed at the Grand Darussalam Syariah Medan hotel where the number is not known with certainty. The sampling technique used is nonprobability sampling. The population in this study is not clearly known, so the type of sampling used is purposive sampling which is taking the subject of research based on the criterias. The Lemeshow formula is used for unknown populations, so the sample in this study was 98 people. The analysis technique used is simple linear regression analysis. The partial and simultaneous test results show that halal tourism has a positive and significant effect on intention to visit. Based on the results of the study it was found that halal tourism gave a variation on intention to visit by 81%.